KORELASI MOTIVASI BERPRESTASI DAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM SEKOLAH MENENGAH ATAS AL-RIFA’IE GONDANGLEGI MALANG - Selina Rahmawati Siswoyo; Ika Ratih Sulistiani; Moh Muslim (VICRATINA, 2020)
This research is backed by the achievement achieved by the class and the motivation achieve such achievement, especially on the subject of Islamic religious education and aims to know there is a correlation between achievement motivation with students’ learning achievement in the subjects of Islamic religious education in Al-Rifa’ie Gondanglegi SMA Malang. The results of this study showed that the motivation of achievement and achievement of lerning students Islamic Education Al-Rifa’ie Gondanglegi Malang in general is quite good, this is seen from the results of a questionnaire with a category of 19 students, the category is consist of 18 students, and from the middle of high category semester exam is 17 students, while the medium category is 20 students The correlation is categorized as an accomplished motivation and student learning achievement in the learning outcomes of Islamic education obtained using the product moment statistical formula approach in the count of IBM SPSS version 20, namely correlation coefficient (Rcount) of 0,448 > 0,325, R table with significant level 0,05. In conclusion there is a positive and significant moderate level relationship between achievement motivation and student learning achievement in Islamic religious education in Al-Rifa’ie Gondanglegi Malang.